Islamic Values in Wood Carving Motifs of Tiang Tongah in Negeri Sembilan Malay Traditional House - Nur Aisyah Safwa Binti Rashidi (Universiti Sains Islam Malaysia, 2024)
Matric: 3202530 (FKAB)-Restricted until Oct 2027